Efficacy and Safety of Finerenone in Chronic Kidney Disease: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Zhang, Ming-Zhu; Bao, Wujisiguleng; Zheng, Qi-Yan; Wang, Ya-Hui; Sun, Lu-Ying (Frontiers in Pharmacology, 2022)
Background Chronic kidney disease (CKD) is a global public health issue. In recent years, the effectiveness of finerenone for treatment of CKD has been the subject of considerable debate. The main objective of the current meta-analysis was to validate the clinical efficacy and safety of finerenone in patients with CKD. Methods Seven databases were searched for randomized controlled trials (RCTs) comparing finerenone with placebo in patients with CKD. Data from eligible studies were extracted and Cochrane risk of bias tool utilized for evaluating the methodological quality of RCTs. The effect size was estimated using risk ratio (RR) and mean difference (MD) with 95% confidence interval (CI). Results Five trials (n = 14335) were included. Compared to placebo groups, the urinary albumin-to-creatinine ratio (UACR) mean ratio from baseline was significantly lower [MD -0.30 (95% CI -0.32, -0.28), P < 0.00001] while decrease in estimated glomerular filtration rate (eGFR) from baseline was significantly higher [MD -2.44 (95% CI -2.82, -2.05), P < 0.00001] for the finerenone groups. Furthermore, the proportion of patients with decreased eGFR (≥ 40%) post-baseline was significantly lower [RR 0.85 (95% CI 0.78, 0.93), P = 0.0002], along with end-stage kidney disease (ESKD) [RR 0.80 (95% CI 0.65, 0.99), P = 0.04] and cardiovascular events (CVs) [RR 0.88 (95% CI 0.80, 0.95), P < 0.003] in the finerenone groups. In terms of safety, the increase in serum potassium concentration and incidence of hyperkalemia were significantly higher for the finerenone groups [MD 0.17 (95% CI 0.10, 0.24), P < 0.00001; RR 2.03 (95% CI 1.83, 2.26), P < 0.00001, respectively], but the incidence of adverse events (AEs) was similar to placebo [RR 1.00 (95% CI 0.98–1.01), P = 0.67]. In all cases, the results were rated as providing moderate quality or high-quality evidence. Conclusion Data from our meta-analysis suggest that finerenone confers significant renal and cardiovascular benefits in patients with CKD. While higher risk of hyperkalemia was observed with finerenone than placebo, differences in AEs were not significant. Finerenone may therefore present a novel promising therapeutic agent for patients with CKD.